2013
DOI: 10.1088/1367-2630/15/4/043026
|View full text |Cite
|
Sign up to set email alerts
|

Truncation identities for the small polaron fusion hierarchy

Abstract: We study a one-dimensional lattice model of interacting spinless fermions. This model is integrable for both periodic and open boundary conditions; the latter case includes the presence of Grassmann valued nondiagonal boundary fields breaking the bulk U (1) symmetry of the model. Starting from the embedding of this model into a graded Yang-Baxter algebra, an infinite hierarchy of commuting transfer matrices is constructed by means of a fusion procedure. For certain values of the coupling constant related to an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…where the parity [|i ] is equal to zero (one) for bosonic (fermionic) indices. (For the details about the algorithm of super tensor product we refer the reader to [25,13]. )…”
Section: )mentioning
confidence: 99%
“…where the parity [|i ] is equal to zero (one) for bosonic (fermionic) indices. (For the details about the algorithm of super tensor product we refer the reader to [25,13]. )…”
Section: )mentioning
confidence: 99%
“…To keep the presentation of our results self-contained we begin by recalling the results of Ref. [19], namely the infinite hierarchy of fused transfer matrices and its truncation for particular values of the anisotropy parameter η. Then we use the truncation identity to rewrite the fusion hierarchy as a higher order functional relation for the transfer matrix (2.4) alone.…”
Section: Functional Relationsmentioning
confidence: 99%
“…, is has been shown that the fused transfer matrices at level n + 1 and n − 1 are related by the truncation identity [19] 6) where the functions φ id n (u), φ τ n (u) are given by the following expressions…”
Section: Fusion Hierarchy and Truncation Identitiesmentioning
confidence: 99%
See 2 more Smart Citations